EFEKTIVTAS ASAM HUMAT DAN BAKTERI PENAMBAT NITROGEN DALAM PERTUMBUHAN BIBIT KOPI ROBUSTA - Anjarsari, Intan Ratna Dewi; Anindya Khairunnisa; Mira Ariyanti (Jurnal Agrotek Tropika, 2025)
Robusta coffee plantations in Indonesia still have low productivity levels compared to other countries such as Vietnam, namely, 0.8 tons/ha and 2.48 tons/ha. One of the factors determining plant productivity is the use of seeds. The seedling phase in coffee plants is an important phase that greatly determines the quality of future plant growth and production. Increasing the growth of the seedling phase is usually done by fulfilling nutrients through the application of inorganic fertilizers. Intensive application of inorganic fertilizers at high doses can accumulate fertilizer residues that harm the soil and the environment. Therefore, it is necessary to optimize the vegetative growth of Robusta coffee in the nursery phase by applying humic acid and Azospirillum sp. This research was conducted in June 2024 - September 2024 in the Ciparanje experimental field of Universitas Padjadjaran . The experimental design used was Randomized Group Design (RBD) with seven treatment combinations and repeated four times, each replicate consisting of three plants. Treatments included control, 40 mL/polybag Azospirillum, 20 mL/polybag Azospirillum, 10 mL/polybag humic acid, 5 mL/polybag humic acid, and a combination. The results showed that the combination of humic acid 10 mL/polybag + Azospirillum 40 mL/polybag had an effect on the increase in the number of leaves but did not show a significant impact on leaf area, chlorophyll index, stem diameter, and Azospirillum population.